2008
DOI: 10.1080/13691180802025681
|View full text |Cite
|
Sign up to set email alerts
|

ELECTED REPRESENTATIVES, ONLINE SELF-PRESENTATION AND THE PERSONAL VOTE:Party, personality and webstyles in the United States and United Kingdom

Abstract: This article examines the way politicians package themselves to their constituents via the Web. It looks at various aspects of online self-promotion by incumbent representatives in two advanced industrial democracies -the US and the UK. It seeks to ascertain the extent to which personal qualities are a key aspect of an elected representative's online persona, and any differences that exist between these democracies with different electoral cultures. It concludes by considering the findings of empirical researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 34 publications
1
40
0
12
Order By: Relevance
“…Second, political actors seek to control the impression they give to maximise the impact on voters (De Landsteer 2004). Whilst the focus for political impression management research has been on how politicians shape perceptions via the media, there is evidence that the Internet may have significant potential as a persuasive channel for shaping perceptions (Stanyer 2008). Specifically considering websites, Stanyer (2008) argues that they provide elected representatives with space to present themselves to constituents.…”
Section: Impression Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, political actors seek to control the impression they give to maximise the impact on voters (De Landsteer 2004). Whilst the focus for political impression management research has been on how politicians shape perceptions via the media, there is evidence that the Internet may have significant potential as a persuasive channel for shaping perceptions (Stanyer 2008). Specifically considering websites, Stanyer (2008) argues that they provide elected representatives with space to present themselves to constituents.…”
Section: Impression Managementmentioning
confidence: 99%
“…Whilst the focus for political impression management research has been on how politicians shape perceptions via the media, there is evidence that the Internet may have significant potential as a persuasive channel for shaping perceptions (Stanyer 2008). Specifically considering websites, Stanyer (2008) argues that they provide elected representatives with space to present themselves to constituents. Gulati (2004), in assessing the use of their websites by members of Congress, found that they sought to promote different images: either as a 'Washington insider' or an 'outsider'.…”
Section: Impression Managementmentioning
confidence: 99%
“…Larsson, 2015;Momoc, 2013;Ross, Fountaine, & Comrie 2015;Zamora Medina & Zurutuza Munoz, 2014). Furthermore, if social media is used to communicate information about the candidate, then this is mostly for the purpose of self-promotion as part of the impression management process (Golbeck, Grimes, & Rogers, 2010;Jackson & Lilleker, 2011;Stanyer, 2008). The second strand of research looks at the interplay of social media and other mediums during campaigns with a focus on the role of social media campaigning within broader political campaign efforts (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…220-221) define political impression management as the employment of political marketing techniques with an aim of positioning candidates in the political sphere and persuading voters of candidates' suitability for political office. Previous studies have identified a range of techniques that politicians may employ in order to try to create a favourable impression during election campaigns, such as revealing details from private life (Langer, 2011;Stanyer, 2008), promoting their skills and virtues, attacking opponents (Edelman, 1988;Franklin, 2004) etc. Before the rise of social media, the major focus of research in political impression management was concerned with politicians' attempts to manage their impression via mass media (Campus, 2010;Lin, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation